Thermal kinetic analysis of the spent mushroom substrate and hydrochar - Kojić Marija (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
A carbon-rich product, hydrochar, was synthesized by hydrothermal carbonization (HTC) of spent mushroom substrate (SMS), at temperature of 260 °C. The thermal kinetic analysis has shown that hydrothermally treatment improve the combustion behavior of hydrochar. The kinetic parameters were determined by Kissinger and Ozawa methods. The SMS-260 had a significantly lower activation energy compared to the SMS, which means that this hydrochar needs a smaller amount of energy to start combustion. Generally, the preliminary results show that HTC is an effective way to transform SMS into alternative solid biofuel.